Implementasi Container Kubernetes untuk Mendukung Scalability - Kezia Yedutun; Agustinus Noertjahyana; Henry Novianus Palit (Jurnal Infra, 2019)
Increasingly advanced technological developments have caused many demands on the client-server to carry out their duties. Existing server capabilities of access that comes from the client. The ability of the server to exceed the limit will experience overload so that many of the adverse effects that will be caused include a decrease in the speed of access even causing a server down.This study tries to propose a solution by providing an additional access point on the server that is using containerization technology on Kubernetes. Where the container is the access point for the client to the server. This containerazitation technology is implemented by utilizing scalability. Scalability in the container will adjust to the needs of the client and server.With container technology, access to the server can be done by adding a container for the access point if it is felt full and will resuce the container if the number of accessing clinets decreases. This will minimize the server overload so that the client can access the server without difficulty due to the lack of access points.